ANNOTATION OF JUDGE'S DECISION NO: 99/G/2020/PTUN-JKT ACCORDING TO THE PERSPECTIVE OF ONRECHTMATIGE OVERHEIDSDAAD - Andrian, Yasmine Putri; An'nissa Dwi Febrianti; Wildan Avie Athoillah (DE'RECHTSSTAAT, 2024)
Judges and prosecutors are law enforcers in Indonesia and are an inseparable part of the court. Both Judges and Prosecutors in exercising their powers and responsibilities must be carried out carefully without any intervention from any party. The accuracy of Judges and Prosecutors in carrying out their duties is needed to avoid the actions of Onrechtmatige Overheidsdaad which can result in injustice. This research was written with the aim of contributing ideas to society in general regarding the annotation of judge decisions according to the Onrechtmatige Overheidsdaad perspective. Onrechtmatige Overheidsdaad has the substance that government actions that violate the law can lead to liability for losses resulting from these actions. This research technique was carried out by collecting data and then compiling it to answer existing problems.